2009 10th International Symposium on Quality of Electronic Design 2009
DOI: 10.1109/isqed.2009.4810396
|View full text |Cite
|
Sign up to set email alerts
|

SEU hardened clock regeneration circuits

Abstract: Single event upsets (SEUs) are becoming increasingly problematic for VLSI circuits due to device scaling, decreasing supply voltages and increasing operating frequencies.To deal with SEUs, radiation hardening is often employed to increase the reliability of VLSI systems. Most existing radiation hardening approaches focus on the combinational or sequential part of the design. Little or no attention has been paid to the impact of radiation particle strikes on the clock network of an IC. Recently, it has been sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…After generating a SET, the transient pulse can propagate through the clock buffers and clock gates depending on the width, the amplitude [7], and the size of the transistor [8]. SET effects can perturb the clock signal generating glitches, jitter [9] and clock skew [10] [13]. Finally the SET may reach one or more registers and change the value of stored data, resulting in a SEU or bit-flip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After generating a SET, the transient pulse can propagate through the clock buffers and clock gates depending on the width, the amplitude [7], and the size of the transistor [8]. SET effects can perturb the clock signal generating glitches, jitter [9] and clock skew [10] [13]. Finally the SET may reach one or more registers and change the value of stored data, resulting in a SEU or bit-flip.…”
Section: Introductionmentioning
confidence: 99%
“…Some techniques have been proposed about radiation hardening in clock buffers like a Hardened Dual Port Inverter [10], SEU Hardened Clock Leaf Inverter [11], and TMR Clock Regenerator Circuit [9]. However, these related works do not always consider in their SET evaluation analysis the variety of parameters in the clock network, such as sizes and types of buffers, the real fan-out of each buffer, clock gating and the capacitance and resistance of the paths.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that clock distribution networks (CDNs) are becoming increasingly vulnerable to transient faults known as single event transients (SETs), owing to technology scaling [1]. In the deep submicron regime, CDNs contribute significantly to the chip-level soft error rate (SER) [2] and radiation particle strikes on the CDN can prove to be catastrophic [3]. Abnormal behaviors in the whole system may be generated if the clock signal is altered by radiation effects [4,5].…”
mentioning
confidence: 99%
“…Although hardening techniques for sequential and combinational circuits have been studied extensively in the past, few research efforts have addressed the problem of radiation hardening in the CDN of an integrated circuit (IC). In the few existing hardened clock circuit designs, Dash et al [3] introduced the triple modulo redundancy (TMR) and split-output single event upset (SEU)-tolerant inverter approaches in the clock regeneration circuit. The split-output-based hardened regenerator will bring about extra delay, reduce the voltage swing, change the duty cycle of the clock signal, and may produce a high-impedance state.…”
mentioning
confidence: 99%
See 1 more Smart Citation